2017
DOI: 10.1590/0100-3984.2016.0054
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic challenge of dizziness: computed tomography and magnetic resonance imaging findings

Abstract: Dizziness is a prevalent symptom in the general population, accounting for a considerable share of physician office visits, and most causes are clinically treatable. It is also a common indication for neuroimaging studies, in order to identify a specific etiology and exclude surgical causes. Here, we illustrate the main peripheral and central causes of dizziness, discussing their possible differential diagnoses, as well as their most important image aspects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
0
6
1
Order By: Relevance
“…It may be suggested that the symptoms progress slowly depending on the penumbra, which enlarges with time in the ischemic events. [27]. In our study, the most common finding was infarction and we did not observe any pathological finding in 27.3 % of the patients.…”
Section: Discussioncontrasting
confidence: 45%
“…It may be suggested that the symptoms progress slowly depending on the penumbra, which enlarges with time in the ischemic events. [27]. In our study, the most common finding was infarction and we did not observe any pathological finding in 27.3 % of the patients.…”
Section: Discussioncontrasting
confidence: 45%
“…17 Other etiologies presenting with dizziness could be neoplastic, vascular, inflammatory, traumatic, or anatomical variations which can be picked up by imaging. 18 In our study, except for patients with the definitive peripheral…”
Section: The Utility Of Checklists In Diagnosismentioning
confidence: 81%
“…Chemoreceptor system tumors such as Glomus jugulotympanicum and Glomus jugulare are considered as primary tumors of the jugular foramen [11]. Metastatic neoplasms and multiple brain lesions must be considered [12]. Viral and bacterial infections must also be evaluated.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Viral labyrinthitis infection that is caused by cytomegalovirus and Rubella is known to induce prenatal hearing loss. Moreover, viral infections are also involved in sudden sensorineural hearing loss [12,13]. Bacterial agents such as Haemophilus influenzae and Streptococcus pneumoniae are typically associated with otomastoditis infections of the mastoid and tympanic cavities.…”
Section: Pathophysiologymentioning
confidence: 99%